Moderating effect of work experience on motivation and performance at Islamic hospital - Chamdan Purnama; Mirhamida Rahmah; Dinda Fatmah; Karina Ananda Putri; Syaiful Hasani; Yusriyah Rahmah; Zakiyah Zulfa Rahmah (Asian Journal of Islamic Management)
Purpose – This study examined the moderating effect of work experience on the relationship between work motivation and employee performance at an Islamic hospital in East Java. It explores how varying levels of experience influence the impact of motivation on performance, providing insights into improving workforce effectiveness. Methodology – An explanatory design was used with a sample of 150 Islamic hospital employees selected using proportional sampling. Data were collected through structured questionnaires using a five-point Likert scale. Multiple and interaction regression analyses were performed using IBM SPSS Statistics version 25 to assess the relationships between work motivation, work experience, and employee performance as well as the moderating role of experience. Findings – The results show a significant positive relationship between work motivation and employee performance, with motivated employees consistently achieving higher performance levels. Work experience significantly moderated this relationship, amplifying the positive effect of motivation on performance. Employees with more experience experienced greater performance improvements when motivated, highlighting the critical role of experience. Implications – These findings provide practical insights for hospital management, suggesting that motivational strategies should consider different levels of experience. Customized training programs, experience-based development, and rewards aligned with work experience can enhance motivation and performance, and improve retention and organizational outcomes. Originality – This study contributes to the existing literature by providing empirical evidence of the moderating effect of work experience on the motivation-performance relationship in the healthcare sector, offering practical recommendations for experience-based employee management development strategies. Motivation strategies to optimize employee performance and enhance organizational outcomes.